2014
DOI: 10.1016/j.bbalip.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic phosphatidic acid and lysophosphatidic acid induce hyaluronic acid synthesis via CREB transcription factor regulation in human skin fibroblasts

Abstract: Cyclic phosphatidic acid (cPA) is a naturally occurring phospholipid mediator and an analog of the growth factor-like phospholipid lysophosphatidic acid (LPA). cPA has a unique cyclic phosphate ring at the sn-2 and sn-3 positions of its glycerol backbone. We showed before that a metabolically stabilized cPA derivative, 2-carba-cPA, relieved osteoarthritis pathogenesis in vivo and induced hyaluronic acid synthesis in human osteoarthritis synoviocytes in vitro. This study focused on hyaluronic acid synthesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 47 publications
1
31
2
Order By: Relevance
“…The signal transduction pathways of PDGFRb (43), LPA 1 (44), and EGFR (45) have all previously been shown to involve the b-arrestins, suggesting that non-cell autonomous fibroblast invasion driven by these mediators will depend on b-arrestin1 and/or -2 as well. Similarly, PDGF-BB, FGF-2, and EGF have all been shown to induce HAS2 expression in human fibroblasts (46), as has LPA (47), suggesting that the HAS2-HA-CD44 pathway described for cell-autonomous invasion may also contribute to the non-cellautonomous fibroblast invasion that we describe here. We believe that further elaboration of the common molecular mechanisms that drive non-cell-autonomous fibroblast invasion in pulmonary fibrosis has the potential to provide a rich set of drug targets for the treatment of IPF and other fibrotic lung diseases.…”
Section: Discussionmentioning
confidence: 77%
“…The signal transduction pathways of PDGFRb (43), LPA 1 (44), and EGFR (45) have all previously been shown to involve the b-arrestins, suggesting that non-cell autonomous fibroblast invasion driven by these mediators will depend on b-arrestin1 and/or -2 as well. Similarly, PDGF-BB, FGF-2, and EGF have all been shown to induce HAS2 expression in human fibroblasts (46), as has LPA (47), suggesting that the HAS2-HA-CD44 pathway described for cell-autonomous invasion may also contribute to the non-cellautonomous fibroblast invasion that we describe here. We believe that further elaboration of the common molecular mechanisms that drive non-cell-autonomous fibroblast invasion in pulmonary fibrosis has the potential to provide a rich set of drug targets for the treatment of IPF and other fibrotic lung diseases.…”
Section: Discussionmentioning
confidence: 77%
“…Because it has been reported that Has2 mRNA expression in fibroblasts depends on ERK signaling (24,35,36), we additionally addressed the question of whether PD98059, a MEK1 inhibitor, was able to prevent Has2 induction in co-culture. However, Has2 mRNA expression was still increased in the co-culture setting.…”
Section: Lef1 Was Required For Has2 Up-regulation In Sf-mentioning
confidence: 99%
“…cPA, which has a sn ‐1 acyl ester bond, was found in myxoamoebae of a true slime mold, Physarum polycephalum , whereas cLyPA has a sn ‐1 alkyl ether bond. While the biological role of cLyPA remains unknown, it may be expected to have various bioactivities like cPA, thus promoting normal cell differentiation and hyaluronic acid synthesis, along with antiproliferative activity in fibroblasts and inhibitory activity toward cancer cell invasion and metastasis …”
Section: Resultsmentioning
confidence: 99%
“…Murofushi et al. reported various bioactivities of cPA, which promotes normal cell differentiation, hyaluronic acid synthesis, antiproliferative activity in fibroblasts, and inhibitory activity toward cancer cell invasion and metastasis . Tsuda et al.…”
Section: Introductionmentioning
confidence: 99%